The Postcolonial Studies Reader - Ashcroft, Bill; Griffiths, Gareth; Tiffin, Helen (London Routledge, 2025)
The essential introduction to the most important texts in post-colonial theory and criticism, this second edition has been thoroughly revised and updated to include 121 extracts from key works in the field. Leading, as well as lesser known figures in the fields of writing, theory and criticism contribute to this inspiring body of work that includes sections on nationalism, hybridity, diaspora and globalization. The Readerʹs wide-ranging approach reflects the remarkable diversity of work in the discipline along with the vibrancy of anti-imperialist writing both within and without the metropolitan centres. Covering more debates, topics and critics than any comparable book in its field, The Post-Colonial Studies Reader is the ideal starting point for students and issues a potent challenge to the ways in which we think and write about literature and culture.
Keywords: History of world literature; English literature; Colonies in literature